2013
DOI: 10.1209/0295-5075/101/16004
|View full text |Cite
|
Sign up to set email alerts
|

Competition between surface relaxation and ballistic deposition models in scale-free networks

Abstract: In this paper we study the scaling behavior of the fluctuations in the steady state WS with the system size N for a surface growth process given by the competition between the surface relaxation (SRM) and the ballistic deposition (BD) models on degree uncorrelated scale-free (SF) networks, characterized by a degree distribution P (k) ∼ k −λ , where k is the degree of a node. It is known that the fluctuations of the SRM model above the critical dimension (dc = 2) scale logarithmically with N on Euclidean lattic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…[6] In 2013, Rocca et al reported a continuous crossover and proposed a scaling involving occurrence probability and system size for a CGM. [7] Xun et al also reported deviation in the scaling exponent values in higher dimensions for the EW universality class in 2015. [8] Also in 2015, Kolakowska and Novotny reported a deviation of scaling exponents along with a new proposed scaling for competitive growth.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[6] In 2013, Rocca et al reported a continuous crossover and proposed a scaling involving occurrence probability and system size for a CGM. [7] Xun et al also reported deviation in the scaling exponent values in higher dimensions for the EW universality class in 2015. [8] Also in 2015, Kolakowska and Novotny reported a deviation of scaling exponents along with a new proposed scaling for competitive growth.…”
Section: Introductionmentioning
confidence: 96%
“…reported a continuous crossover and proposed a scaling involving occurrence probability and system size for a CGM. [ 7 ] Xun et al. also reported deviation in the scaling exponent values in higher dimensions for the EW universality class in 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Basic models include random deposition (RD), ballistic deposition (BD), random deposition with surface relaxation (RDSR), and solid-on-solid (SoS) [4]. Competitive Growth Models (CGM) are developed for a more precise description of thin film growth that incorporates more than one discrete growth mechanism in a single growth process [5][6][7].…”
Section: Introductionmentioning
confidence: 99%